Effect of Cooling Blanket on the Heat Stress of Horses in Hot and Humid Environments - Yuki Ojima; Suzuka Torii; Yosuke Maeda; Akihiro Matsuura (Animals, 2022)
Heat stress is serious problem for livestock. While riding horses and racehorses spend the majority of their days in stalls, there are few reports on effective methods for reducing stall heat stress. The aim of the present study was to evaluate the effectiveness of an ice horse blanket in hot and humid environments. Twenty healthy horses were measured first without the blanket (C) and then measured with the blanket (IB), or vice versa, in a cross-over trial. The blanket was designed to keep cooling the front back, the rear back, and the loin. Skin surface temperature, respiratory rate, rectal temperature, and plasma cortisol level in both C and IB were measured at 10:00, 12:30, and 15:00. The skin surface temperature of the front back was decreased with cooling time in IB, whereas it was not changed in C. Similarly, heart rate, respiratory rate, and plasma cortisol level also decreased only in IB. The blanket used in the present study had the advantage of allowing for gentle cooling of the horse’s body without the use of water or fans. Applying this methodology should enable effective reduction of heat stress not only in horses but also in other mammals kept in barns.